Augmented Reality Game-Based Learning: Enhancing Basic Mathematics Abilities for Students with Special Needs - Ferawati, Ferawati; Saputri, Fiqih Hana; Stianingsih, Lilis; Putri, Eka Uliyanti; Sofia, Detin; Hanafri, Muhammad Iqbal (Jurnal Pendidikan MIPA, 2024)
Basic math skills are very important not only for students in general, but also for those with special needs. Students can learn math in a fun way through an engaging learning medium, one of which is augmented reality game-based learning can help students face challenges in understanding basic math concepts. This research aims to develop valid, practical and effective augmented reality learning media applications. The type of research applied is research and development (R & D) with the development of 4D models. The Data collection techniques and instruments include validation sheets, practicality sheets, tests, observations, interviews, questionnaires and documentation. The research sample encompasses 12 students sitting in grade 5 at SKh YKDW 01 Tangerang.  The results of the research show that : (1) The validity of the augmented reality learning application meets the very valid criteria. (2) The augmented reality learning application is found to be very practical. (3) The results of product effectiveness analysis were obtained from test results and student responses in questionnaire sheets N-Gain score bearing 0.84 in the high category with indicators: the utilizing and understanding application devices, the ease of access and use, the students engagement and motivation, and the supporting collaborative learning. Additionally, these affirm that the AR is very effective in increasing the engagement, understanding, and math skills of children with special needs. Therefore, the designed augmented reality learning media are suitable for improving the basic mathematical abilities of children with special needs.       Keywords: math, AR, student special need.DOI: http://dx.doi.org/10.23960/jpmipa/v25i3.pp1378-1396